The inclusion of children in preschool institutions and the family - Aleksić, Adrijana A.; Mitrović, Sanja M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
Inclusion in preschool institutions significantly impacts the socialization and development of children with developmental difficulties, allowing them to participate in everyday activities. For its successful and functional implementation, collaboration and partnership among parents, preschool teashers, and specialists, as well as the involvement of individual assistants for better support, are essential. If preschool teachers are insufficiently trained to work with children with developmental difficulties, it hinders the realization of activities. Integration is achieved by establishing developmental groups, which fosters the desire for parents to accept that their child has developmental difficulties. Acceptance influences the quality of parental care and the child’s development, while rejection and denial of difficulties prevent the child’s progress. Establishing partnerships between preschool institutions, families, and other social factors improves and supports inclusive practices. The partnership must be based on respect and the active involvement of parents, who play a crucial role in the development of their children. All children, including those with difficulties, deserve equal opportunities for progress and socialization.